Net gain: seeking better outcomes for local people when mitigating biodiversity loss from development - Jones, J; Bull, J; Roe, D; Baker, J; Griffiths, VF; Starkey, M; Sonter, L; Milner-Gulland, E (Elsevier, 2019)
Economic development projects are increasingly applying the mitigation hierarchy to achieve No Net Loss, or even a Net Gain, of biodiversity. Because people value biodiversity and ecosystem services, this can affect the wellbeing of local people, however these types of social impacts from development receive limited consideration. We present ethical, practical and regulatory reasons why development projects applying the mitigation hierarchy should consider related social impacts. We highlight risks to local wellbeing where projects restrict access to biodiversity and ecosystem services in biodiversity offsets. We then present a framework laying out challenges and associated opportunities for delivering better biodiversity and local wellbeing outcomes. Greater coordination between social and biodiversity experts, and early and effective integration of local people in the process, will ensure that efforts to reduce the negative impacts of development on biodiversity can contribute to, rather than detract from, local people’s wellbeing.